Professor Knight on Limits to the Use of Capital - Wright, David McCord (Quarterly Journal of Economics, 1944)
Scope of the paper, 331. — I. Assumptions, 333. — Standard of living, 334. — Limit to the use of capital, 334. — The problem of steady development, 336. — The rate of accumulation, 337. — II. Possible objections, 339. New capital needs, 340. — III. Assuming many varieties of capital goods and of consumer's goods, 341. — "Diminishing Returns, " 342. — Standard of living, 344. — IV. Alleged "twilight zone" above zero per cent, 346. — Brakes upon borrowing, 347. — Effect upon demand for capital, 348. — The condition of indefinite waste, 349. — Perfectly elastic demand, 350. — V. Demand for "satisfactions in general, " 352. — "Hoped-for security, " 354. — VI. Summary of conclusions, 356.